A Aktivitas Antibakteri Ekstrak Daun Kopi Aranio (Coffea canephora ) Terhadap Bakteri Propionibacterium Acnes: Aktivitas Antibakteri Ekstrak Daun Kopi Aranio (Coffea canephora ) Terhadap Bakteri Propionibacterium Acnes - Rahmah, Aulia; Nastiti, Kunti; Mahdiyah, Dede; Darsono, Putri Vidiasari (LPPM Universitas Sari Mulia, 2023)
Background: Acne is a skin disease due to chronic inflammation with complex pathogenesis, excessive bacterial colonization, and inflammation. One of the causes of acne is due to excessive sebum gland activity and is exacerbated by bacterial infection, one of the bacteria that causes acne is Propionibacterium acnes. Coffee leaves are used by the community, especially in Babayau Village, Balangan Regency, South Kalimantan, to treat acne naturally and traditionally by mixing the cleaned coffee leaves with wet powder and then rubbing it evenly all over the face. Objective: Knowing the effectiveness of coffee leaf extract (Coffea canephora) in inhibiting the growth of Propionibacterium acnes bacteria, and knowing the Minimum Inhibitory Concentration and Minimum Bactericidal Concentration against Propionibacterium acnes bacteria. Methods: The type of research to test the antibacterial activity of aranio coffee leaf extract against Propionibacterium acnes bacteria was true expertimental with a post test only control group design, control group 100%, 75%, 50% and 25%, negative control using DMSO, positive control with clindamycin. Screening for antibacterial activity of aranio coffee leaf extract using the disc diffusion method and determining the Minimum Inhibitory Concentration and Minimum Bactericidal Concentration using the dilution method. Results: Coffee leaf extract (Coffea canphora) contains secondary metabolites, namely flavonoids, tannins, and saponins which have antibacterial activity. The antibacterial activity test of coffee leaf extract (Coffea canphora) in the disc diffusion method had an inhibition zone of 27.86 ± 2.14 while in the dilution method the Minimum Inhibitory Concentration (MIC) was at a concentration of 75% and did not have a Minimum Bactericidal Concentration (MBC). Conclusion: Coffee leaf extract (Coffea canphora) can inhibit Propionibacterium acnes at a concentration of 75%, and cannot kill Propionibacterium acnes.